Collaborating for Results : Silo Working and Relationships that Work. - Willcock, David Ian (Ashgate Publishing Ltd, 2013)
Collaborating for Results focuses on the human reasons for unproductive silo working in organisations, combining psychology with organisation development theory and practice. The central theme is that a visible agenda for building and maintaining working relationships across organisations is required by those seeking competitive advantage. It describes the contours of working relationships at three levels - individual, team and organisation - and proposes practical actions en route to collaboration and high performance. In doing so it acknowledges the complexity of people and relationships, th.